Physicians’ Perceptions of the Quality of Palliative Care and of the Importance of Collaboration in Interdisciplinary Teams in Norwegian Nursing Homes - Skomakerstuen Ødbehr L; Hov R; Sanaker H; Sandsdalen T (Journal of Multidisciplinary Healthcare)
Liv Skomakerstuen Ødbehr,1,* Reidun Hov,2,* Harald Sanaker,3,* Tuva Sandsdalen1,* 1Department of Health and Nursing Sciences, Faculty of Social and Health Sciences, University of Inland Norway, Elverum, Norway; 2Centre for Development of Institutional and Home Care Services Inland (Hedmark) Norway, Hamar Municipality, Norway; 3Municipal Medical Center, Ringsaker Municipality, Brumunddal, Norway*These authors contributed equally to this workCorrespondence: Liv Skomakerstuen Ødbehr, Faculty of Social and Health Sciences, University of Inland Norway, Post Box 400, Elverum, 2418, Norway, Tel +47 959 079 84, Email liv.odbehr@inn.noPurpose: The palliative phase of a patient’s life is often characterized by disease complexity, increasing the need for holistic care, support for the patient’s relatives, and the up-to-date knowledge of a multidisciplinary healthcare team. Physicians in nursing homes have the main responsibility for providing palliative care to vulnerable and fragile patients. There is limited research uncovering physicians’ experience and perceptions of what is important in this phase of patients’ lives. The aim of the study was thus to investigate physicians’ perceptions of factors that influence the quality of palliative care in Norwegian nursing homes and their descriptions of the importance of the team’s collaboration.Materials and Methods: The study has a qualitative research design based on interviews with twelve nursing home physicians in Eastern Norway. Interviews were conducted between February 2023 to May 2023, analyzed using qualitative content analysis.Results: Three themes describe the content of the findings: i) Comprehensive care plans enhance the quality of palliative care, ii) A collaborative team provides higher-quality care than the sum of its parts, iii) Systemic and environmental factors affect the ability to ensure continuity of care.Conclusion: The physicians in this study expressed that the quality of palliative care in nursing homes depended on comprehensive care plans, including up-to-date knowledge of medical treatment options, partnership with the patient and relatives, and a consistent holistic approach to the patient. The quality also depended on the interdisciplinary team’s collaboration in assessing the patient, observing symptoms, and planning further care and treatment in accordance with patients’ and their relatives’ preferences and wishes. Finally, systemic and environmental factors affected the ability to ensure continuity of care. Further work is needed to ensure that systemic factors enable physicians to deliver high-quality palliative care and that a comfortable physical environment is created in nursing homes.Plain language summary: In this study, we interviewed twelve nursing home physicians and asked them about their views on the quality of palliative care in nursing homes and what they thought about the importance of working in interdisciplinary teams to provide the best possible care for patients. The interviews were conducted face-to-face at the physicians’ workplace. All interviews were recorded on audio files, transcribed and analyzed using content analysis. The physicians said that they valued cooperating and exchanging expertise in an interdisciplinary team. As they had little time available for each patient, the team’s efforts were invaluable. The quality of care depended on good observations by healthcare professionals, as well as follow-up actions. The quality was good when the collaboration worked. Also, important for maintaining good quality were different aspects of the healthcare system, and a suitable physical environment that made patients and relatives feel cared for. The findings of this study show that there is a need for interprofessional expertise and that each member of the team is important for the best possible outcome. Good cooperation depends on openness and respect, especially in difficult issues where there are disagreements or different views on how to solve a particular case. This study shows that good and sufficient resources improve care, especially when the interdisciplinary team works well together.Keywords: palliative care, nursing homes, physicians, end-of-life, health personnel